Profession-Specific Curriculum Design in Mathematics Teacher Education: Connecting Disciplinary Practice to the Learning of Group Theory - Wessel, Lena; Leuders, Timo (Practice-Oriented Research in Tertiary Mathematics Education)

Civic Statistics for Prospective Teachers: Developing Content and Pedagogical Content Knowledge Through Project Work - Podworny, Susanne; Frischemeier, Daniel; Biehler, Rolf (Statistics for Empowerment and Social Engagement)

Data Visualization Packages for Non-inferential Civic Statistics in High School Classrooms - Frischemeier, Daniel; Podworny, Susanne; Biehler, Rolf (Statistics for Empowerment and Social Engagement)

An example of rich, real and multivariate survey data for use in school - Podworny, Susanne; Fleischer, Yannik; Stroop, Dietlinde; Biehler, Rolf

From private digital platforms to public data spaces: implications for the digital transformation - Beverungen, Daniel; Hess, Thomas; Köster, Antonia; Lehrer, Christiane (Electronic Markets)
Technological developments such as Cloud Computing, the Internet of Things, Big Data and Artificial Intelligence continue to drive the digital transformation of business and society. With the advent of platform-based ecosystems and their potential to address complex challenges, there is a trend towards greater interconnectedness between different stakeholders to co-create services based on the provision and use of data. While previous research on digital transformation mainly focused on digital transformation within organizations, it is of growing importance to understand the implications for digital transformation on different layers (e.g., interorganizational cooperation and platform ecosystems). In particular, the conceptualization and implications of public data spaces and related ecosystems provide promising research opportunities. This special issue contains five papers on the topic of digital transformation and, with the editorial, further contributes by providing an initial conceptualization of public data spaces' potential to foster innovative progress and digital transformation from a management perspective.
Keywords: Digital transformation; Public data spaces; Digital platforms; GAIA-X

Systematizing the lexicon of platforms in information systems: a data-driven study - Bartelheimer, Christian; zur Heiden, Philipp; Lüttenberg, Hedda; Beverungen, Daniel (Electronic Markets)
While the Information Systems (IS) discipline has researched digital platforms extensively, the body of knowledge appertaining to platforms still appears fragmented and lacking conceptual consistency. Based on automated text mining and unsupervised machine learning, we collect, analyze, and interpret the IS discipline’s comprehensive research on platforms—comprising 11,049 papers spanning 44 years of research activity. From a cluster analysis concerning platform concepts’ semantically most similar words, we identify six research streams on platforms, each with their own platform terms. Based on interpreting the identified concepts vis-à-vis the extant research and considering a temporal perspective on the concepts’ application, we present a lexicon of platform concepts, to guide further research on platforms in the IS discipline. Researchers and managers can build on our results to position their work appropriately, applying a specific theoretical perspective on platforms in isolation or combining multiple perspectives to study platform phenomena at a more abstract level.
Keywords: Platform; Text mining; Machine learning; Data communications; Interpretive research; Systems design and implementation

Self-regulated learning in a mathematics course for engineers in the first semester: insights into students reported resource management and cognitive strategies - Kolbe, Tim; Wessel, Lena (Fourth conference of the International Network for Didactic Research in University Mathematics)

Mahr, Melanie: Reden ist Gold... – vom Umgang mit Sexualität bei Jugendlichen. Eine empirisch-qualitative Studie zur Situation der Sexualpädagogik im Kontext katholischer, vollstationärer Einrichtungen der Kinder- und Jugendhilfe. – Würzburg: Echter Verlag 2020 (=Studien zur Theologie und Praxis der Caritas und Sozialen Pastoral, 40) - Reis, Oliver (Theologische Revue)

Wann ist eine Differenz diskriminierend? Das Oszillieren zwischen Unterschieden und Ungleichheiten in der katholischen Gemeindearbeit - Hofmeister, Lisa; Reis, Oliver (Der Vielfalt Raum geben. Zum ambivalenten Potenzial einer differenzsensiblen Kirche)

Wie steht es mit der Situationsorientierung der Religionspädagogik? - Mellentin, Franziska; Reis, Oliver (unterwegs 2/2022)

Schulbuch - Rakowski, Jana; Reis, Oliver (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)

Vorlesen - Reis, Oliver; Saß, Katharina (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)

Kerze - Reis, Oliver; Wittke, Annika (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)

Beten - Meditieren - Reis, Oliver (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)

Segnen - Reis, Oliver (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)

„Warum können wir denn jetzt nicht sagen, dass die Sophia wirklich Recht hat?“ Norm und Relativierung in religionspädagogischen Bildungsprozessen - Reis, Oliver; Roose, Hanna (Relativität und Bildung. Fachübergreifende Herausforderungen und fachspezifische Grenzen)

Religiöse Bildung als Medium der Kirchenmodernisierung und der Kirchenrestauration - Reis, Oliver; Tomberg, Markus (Aufbruch statt Rückzug. Die römisch-katholische Kirche in der Öffentlichkeit heute)

„In Erinnerung geblieben sind mir die ritualartigen Dinge“. Rituale und ihre eigensinnige Mitarbeit am nachhaltigen Lernen - Reis, Oliver; Weber, Carla (Jahrbuch für Konstruktivistische Religionsdidaktik)

Den roten Faden selbst in der Hand – Ritualisierte Selbstorganisation als Wirkungsfaktor im Paderborner Reli-Fächer - Reis, Oliver; Walter, Marie (Jahrbuch für Konstruktivistische Religionsdidaktik)

Behinderung / Inklusion - Brandstetter, Bettina; Reis, Oliver (Ethische Kernthemen. Lebensweltlich – theologisch-ethisch – didaktisch)

Akteur-Netzwerk-Theorie - Reis, Oliver (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)

Nachhaltige Wirkung von Religionsunterricht

Religionsunterricht beobachten. Praktiken – Artefakte – Akteure

Weltanschauliche, religiöse oder theologische Positionalität – Positionalität als Lösung und Problem der KJT im Zueinander von Tradition und subjektiven Überzeugungen - Reis, Oliver („Hauptsache, du hast eine Meinung und einen eigenen Glauben“ Positionalität (nicht nur) in der Kinder- und Jugendtheologie)

Acquiring religious words: Dialogical and individual construction of the word’s meaning - Viertel, Franziska; Reis, Oliver; Rohlfing, Katharina (Philosophical Transactions of the Royal Society B)

Auf die Position kommt es an?! Theologische Gespräche im Religionsunterricht und die Herausforderung der Positionalität - Reis, Oliver; Roose, Hanna (Lesepause. Magazin für alle, die im Erzbistum Paderborn Religion unterrichten)

Was meint Digitalisierung und was hat das mit dem RU zu tun? - Büttner, Gerhard; Reis, Oliver (KatBl)

Kompetenzorientiere Aufgabenformate im Distanzunterricht?! - Reis, Oliver; Woppowa, Jan (KatBl)

Der Distanzunterricht als digitalisierender Kurzschluss - Woppowa, Jan; Reis, Oliver (KatBl)

Artefakte als (An-)Zeiger der Zeit. Praxistheoretische Analysen zu religiösen Artefakten an einer Katholischen Schule - Hoyer, Isabelle; Reis, Oliver

Lernstandserhebung/-diagnostik, wissenschaftstheoretisch - Reis, Oliver (WiReLex 2/2022)

Nutritional Assessment of Ready-to-Eat Salads in German Supermarkets: Comparison of the nutriRECIPE-Index and the Nutri-Score - Schlarbaum, Laura; Forner, Frank; Bohn, Kristin; Amberg, Michael; Mäder, Patrick; Lorkowski, Stefan; Meier, Toni (Foods)
Globally, an unbalanced diet causes more deaths than any other factor. Due to a lack of knowledge, it is difficult for consumers to select healthy foods at the point of sale. Although different front-of-pack labeling schemes exist, their informative value is limited due to small sets of considered parameters and lacking information on ingredient composition. We developed and evalauated a manufacture-independent approach to quantify ingredient composition of 294 ready-to eat salads (distinguished into 73 subgroups) as test set. Nutritional quality was assessed by the nutriRECIPE-Index and compared to the Nutri-Score. The nutriRECIPE-Index comprises the calculation of energy-adjusted nutrient density of 16 desirable and three undesirable nutrients, which are weighted according to their degree of supply in the population. We show that the nutriRECIPE-Index has stronger discriminatory power compared to the Nutri-Score and discriminates as well or even better in 63 out of the 73 subgroups. This was evident in groups where seemingly similar products were compared, e.g., potato salads (Nutri-Score: C only, nutriRECIPE-Index: B, C and D). Moreover, the nutriRECIPE-Index is adjustable to any target population’s specific needs and supply situation, such as seniors, and children. Hence, a more sophisticated distinction between single food products is possible using the nutriRECIPE-Index.

E-Assessment zwischen Kompetenzorientierung und Technologieskepsis:Entwicklung eines Tools zur Messung musikalischer Fähigkeiten im Unterricht - Neuhausen, Timo (Beiträge empirischer Musikpädagogik)

Evaluation von Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Schürmann, Mirko; Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schaper, Niclas; Biehler, Rolf; Hochmuth, Reinhard (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

PATTERNS 2022 The Fourteenth International Conferences on Pervasive Patterns and Applications

Effects of drawing instructions and strategic knowledge on mathematical modeling performance: Mediated by the use of the drawing strategy - Schönherr, Johanna; Schukajlow, S.; Blomberg, J.; Leopold, C. (Applied Cognitive Psychology, ac3930)

Drawing instructions, strategic knowledge, strategy-based motivation, and students' use of drawings - Schönherr, Johanna; Schukajlow, S.; Leopold, C. (Proceedings of the 45th PME Conference)

Die Kommanditistenhaftung in der GmbH & Co. KG vor Registereintragung - Eine Untersuchung auf der Grundlage Digitaler Rechtstatsachenforschung - Bartlitz, David (Neue Zeitschrift für Gesellschaftsrecht (NZG))

Die Gesellschafterstruktur der GmbH & Co. KG aus der Perspektive der Digitalen Rechtstatsachenforschung - Bartlitz, David; Bohnert, Alexander (Zeitschrift für Wirtschaftsrecht (ZIP))

Die Begebung elektronischer Wertpapiere - Bartlitz, David (Neue Juristische Wochenschrift (NJW))

“Free” as in Freedom to Protest? - Massacci, Fabio; Sabetta, Antonino; Mirkovic, Jelena; Murray, Toby; Okhravi, Hamed; Mannan, Mohammad; Rocha, Anderson; Bodden, Eric; Geer, Daniel E. (IEEE Security & Privacy)

Transdisziplinäre Eventforschung als Möglichkeitswissenschaft. Überlegungen zum Vermittlungs- und Moderationspotential von Events - Flath, Beate (Druckwellen. Eskalationskulturen und Kultureskalationen in Pop, Gesellschaft und Politik)

Transitivity in finite general linear groups - Ernst, Alena; Schmidt, Kai-Uwe (arXiv:2209.07927)
It is known that the notion of a transitive subgroup of a permutation group $G$ extends naturally to subsets of $G$. We consider subsets of the general linear group $\operatorname{GL}(n,q)$ acting transitively on flag-like structures, which are common generalisations of $t$-dimensional subspaces of $\mathbb{F}_q^n$ and bases of $t$-dimensional subspaces of $\mathbb{F}_q^n$. We give structural characterisations of transitive subsets of $\operatorname{GL}(n,q)$ using the character theory of $\operatorname{GL}(n,q)$ and interprete such subsets as designs in the conjugacy class association scheme of $\operatorname{GL}(n,q)$. In particular we generalise a theorem of Perin on subgroups of $\operatorname{GL}(n,q)$ acting transitively on $t$-dimensional subspaces. We survey transitive subgroups of $\operatorname{GL}(n,q)$, showing that there is no subgroup of $\operatorname{GL}(n,q)$ with $1<t<n$ acting transitively on $t$-dimensional subspaces unless it contains $\operatorname{SL}(n,q)$ or is one of two exceptional groups. On the other hand, for all fixed $t$, we show that there exist nontrivial subsets of $\operatorname{GL}(n,q)$ that are transitive on linearly independent $t$-tuples of $\mathbb{F}_q^n$, which also shows the existence of nontrivial subsets of $\operatorname{GL}(n,q)$ that are transitive on more general flag-like structures. We establish connections with orthogonal polynomials, namely the Al-Salam-Carlitz polynomials, and generalise a result by Rudvalis and Shinoda on the distribution of the number of fixed points of the elements in $\operatorname{GL}(n,q)$. Many of our results can be interpreted as $q$-analogs of corresponding results for the symmetric group.

Emotion Recognition, Empathy, or ToM? The Influence of Social Cognition on Communication in Traumatic Brain Injury - Quinting, Jana; Jonas, Kristina; Kuhn, Charlotte; Stenneken, Prisca (Zeitschrift für Neuropsychologie)
Abstract: Communication disorders following traumatic brain injury have been attributed to social-cognitive dysfunctions. However, this relationship is not always clearly demonstrated in empirical research. This systematic review seeks to clarify the relationship by considering different subcomponents of social cognition and communication. The results show that, for the social-cognitive subcomponents of emotion recognition and empathy, evidence is available mainly for a relationship to global communication abilities. However, we did find a systematic relationship between Theory of Mind and individual aspects of pragmatics (i. e., the processing of irony/sarcasm, insincerity, indirect speech acts). To strengthen the evidence for the role of social-cognitive subcomponents concerning communication, future research could implement a core outcome set based on the present findings.

Digital Assessment of Acquired Alexia and Agraphia: On the Relevance of Written Discourse - Jaecks, Petra; Jonas, Kristina (Frontiers in Communication)
The digital revolution has created challenges as well as opportunities for people with acquired reading (= alexia) and writing (= agraphia) impairments. Although it is difficult to validly assess written discourse, it is imperative that people with alexia and agraphia (PwAA) receive reliable diagnostics for the following reasons: (1) discourse in written and oral forms is highly relevant to daily interaction and participation, but there are no established tests or diagnostic procedures to assess written discourse; (2) reliable diagnostic measures are a prerequisite for any language rehabilitation, especially for the complex skills needed for written discourse; and (3) the continuing trend in digitalization offers new opportunities for easily collecting and assessing written discourse via digital means. In our manuscript, we highlight the relevance of written discourse for social participation and in the digital world and argue that in order to improve social participation in general and digital participation in particular for PwAA, remote assessment of written discourse abilities can be the basis for speech and language therapy treatment focused on communicative abilities.

Measuring Verbal Reasoning and Executive Strategies in German Speaking People with Cognitive-Communication Disorders: Cross-Cultural Adaptation and Pilot Testing of the FAVRES-DE - Quinting, Jana; Stenneken, Prisca; Mahlke, Anne; de Beer, Carola; Hogrefe, Katharina; Hussmann, Katja; Baumgaertner, A.; MacDonald, Sheila; Jonas, Kristina (Aphasiology)

Lesen und Schreiben: digital. Praxis Deutsch 292

POPulismus, POPkultur und Pop-Didaktik. - Klingmann, Heinrich (Druckwellen. Eskalationskulturen und Kultureskalationen in Pop, Gesellschaft und Politik.)

High resolution off resonant spectroscopy as a probe of the oxidation state - Nowakowski, Michał; Kalinko, Aleksandr; Szlachetko, Jakub; Fanselow, Rafał; Bauer, Matthias (Journal of Analytical Atomic Spectrometry)
Currently, chemistry and physics are strongly dependent on the concept of the oxidation state. While the formal oxidation state is easily evaluated, the real physical oxidation state value is often difficult to determine and significantly varies from the formal values. Determination of the ionization threshold in X-ray absorption spectroscopy (XANES) relies on the absorption edge position and sometimes poses limitations, mainly due to the edge resonances. Moreover, the lower energy states can be probed only within x-soft or XUV photons providing only surface state information of probed materials. Here, we employ high energy resolution off-resonant spectroscopy to determine both 1s and 3p binding energies of Fe-based materials and therefore correlate to their physical oxidation state. The results are compared to the ones obtained with classical X-ray absorption, X-ray emission, and photoelectron spectroscopies. The observed differences in binding energies are discussed in a frame of initial and final state interactions with the atom's electronic configurations. The presented methodology is discussed towards potential use to single-shot experiments and application at X-ray free-electron lasers. Alternatively, core level X-ray emission spectroscopy can be used, but the emission line positions are strongly affected by spin-orbit interaction. However, due to the energy transfer from the photon to the excited core electron, the same information as in XANES is probed in high energy resolution off-resonant spectroscopy (HEROS). Based on the Kramers–Heisenberg theory, we propose a new approach for ionization threshold determination which is free of the limitations encountered in XANES-based determination of the core state energy. Namely, the value of core state energy can be determined analytically using a few HEROS spectra recorded with significantly higher spectral resolution. This approach provides a basis for the universal physical oxidation state determination method.
Keywords: Spectroscopy; Analytical Chemistry

Zwischen teilhaben und Teil sein. Ein Gespräch über kulturelle Teilhabe im Kontext transdisziplinärer Forschung - Flath, Beate; Momen Pour Tafreshi , Maryam (Transformational POP: Transitions, Breaks, and Crises in Popular Music (Studies) (Vibes - The IASPM D-A-CH Series 2))